Chromosomal location of genomic SSR markers associated with yellow rust resistance in Turkish bread wheat (Triticum aestivum L.) - AYDİN, YILDIZ (INDIAN ACAD SCIENCES, 2013)
We have previously reported Xgwm382 as a diagnostic marker for disease resistance against yellow rust in Izgi2001 x ES14 F-2 population. Among the same earlier tested 230 primers, one SSR marker (Xgwm311) also amplified a fragment which is present in the resistant parent and in the resistant bulks, but absent in the susceptible parent and in the susceptible bulks. To understand the chromosome group location of these diagnostic markers, Xgwm382 and Xgwm311, in the same population, we selected 16 SSR markers mapped only in one genome of chromosome group 2 around 1-21 cM distance to these diagnostic markers based on the SSR consensus map of wheat. Out of 16 SSRs, Xwmc658 identified resistant F-2 individuals as a diagnostic marker for yellow rust disease and provided the location of Xgwm382 and Xgwm311 on chromosome 2AL in our plant material.
Keywords: yellow rust; microsatellite marker; chromosomal location; 2AL; wheat; BULKED SEGREGANT ANALYSIS; HEAD BLIGHT RESISTANCE; F-SP TRITICI; POWDERY MILDEW; MICROSATELLITE MARKERS; COMMON WHEAT; PUCCINIA-STRIIFORMIS; DISEASE-RESISTANCE; RUSSIAN WHEAT; GENE